Pidana Dalam Hukum Islam Dan Perbandingan Dengan Hukum Pidana Nasioual - prasetyo, teguh (Jurnal Hukum IUS QUIA IUSTUM, 2016)
The traditional criminal which originates from Isiamic Fiqh has a great philosophical basic to be the source of the national criminal law reform in Indonesia. However, it is relevant to seeks the religious values to establish the new Criminal Law.